2020
DOI: 10.1029/2020gl087232
|View full text |Cite
|
Sign up to set email alerts
|

The Double‐ITCZ Bias in CMIP3, CMIP5, and CMIP6 Models Based on Annual Mean Precipitation

Abstract: The double-intertropical convergence zone (ITCZ) bias is one of the most outstanding errors in all previous generations of climate models. Here, the annual double-ITCZ bias and the associated precipitation bias in the latest climate models for Coupled Model Intercomparison Project (CMIP) Phase 6 (CMIP6) are examined in comparison to their previous generations (CMIP Phase 3 [CMIP3] and CMIP Phase 5 [CMIP5]). All three generations of CMIP models share similar systematic annual multi-model ensemble mean precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
152
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(167 citation statements)
references
References 53 publications
6
152
0
Order By: Relevance
“…More sophisticated feedback analysis revealed that the reduction of ENSO variability is due to either the increase of the negative feedback by the mean current thermal advec-tion (An and Bong, 2018) or the reduction of the major positive feedback processes (thermocline, zonal advection and Ekman feedbacks) (Chen et al, 2019a;Tian et al, 2017). The negative feedback due to the thermal advection by the mean current was intensified by the stronger cross-equatorial winds associated with the northward migration of the ITCZ (e.g.…”
Section: Mechanisms and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated feedback analysis revealed that the reduction of ENSO variability is due to either the increase of the negative feedback by the mean current thermal advec-tion (An and Bong, 2018) or the reduction of the major positive feedback processes (thermocline, zonal advection and Ekman feedbacks) (Chen et al, 2019a;Tian et al, 2017). The negative feedback due to the thermal advection by the mean current was intensified by the stronger cross-equatorial winds associated with the northward migration of the ITCZ (e.g.…”
Section: Mechanisms and Discussionmentioning
confidence: 99%
“…Such distinct changes in ENSO characteristics through the 20th and 21st centuries may be related to low-frequency modulation by natural variability or the global warming trend due to increasing greenhouse gas concentrations, or a combination of natural and anthropogenic factors (e.g. An et al, 2008;Cai et al, 2015a;Collins, 2000;Gergis and Fowler, 2009;Timmermann et al, 1999;Trenberth and Hoar, 1997;Yang et al, 2018;Yeh et al, 2014;Yeh and Kirtman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We evaluate next the problems still encountered by CMIP5 models in reproducing key aspects of tropical dynamics (Tian & Dong, 2020). Averaging the data over the Tropics, we obtain the ranking on the vertical axis in Figure 1.…”
Section: Ranking the Modelsmentioning
confidence: 99%
“…Precipitation simulation and projection in global climate models (GCMs) are of great scientific and societal interest. Although some impressive improvements have been made in recent decades (e.g., Wang et al., 2016; Xie et al., 2019; G. J. Zhang & Wang, 2006), GCMs, to some extent, are still suffering from many deficiencies (e.g., weak synoptic and intraseasonal variabilities, the double Intertropical Convergence Zone, and underestimated precipitation extremes) in various aspects of precipitation simulation (Flato et al., 2013; Lin et al., 2006; Tian & Dong, 2020; Zhang et al., 2013), among which the biases over some land areas (e.g., southern China, central India, and the US Great Plains) are stubborn (Harding et al., 2013; Huang et al., 2013; Koutroulis et al., 2016; Kumar et al., 2014; Mehran et al., 2014; Phillips & Gleckler, 2006).…”
Section: Introductionmentioning
confidence: 99%